Dendritic Architecture Predicts in vivo Firing Pattern in Mouse Ventral Tegmental Area and Substantia Nigra Dopaminergic Neurons - Trinidad Montero (Frontiers Media S.A., 2021)
The firing activity of ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) dopaminergic (DA) neurons is an important factor in shaping DA release and its role in motivated behavior. Dendrites in DA neurons are the main postsynaptic compartment and, along with cell body and axon initial segment, contribute to action potential generation and firing pattern. In this study, the organization of the dendritic domain in individual VTA and SNc DA neurons of adult male mice, and their relationship to in vivo spontaneous firing, are described. In comparison with dorsal VTA DA neurons, ventrally located VTA neurons (as measured by cell body location) possess a shorter total dendritic length and simpler dendritic architecture, and exhibit the most irregular in vivo firing patterns among DA neurons. In contrast, for DA neurons in the SNc, the higher irregularity of firing was related to a smaller dendritic domain, as measured by convex hull volumes. However, firing properties were also related to the specific regional distribution of the dendritic tree. Thus, VTA DA neurons with a larger extension of their dendritic tree within the parabrachial pigmented (PBP) nucleus fired more regularly compared with those with relatively more dendrites extending outside the PBP. For DA neurons in the SNc, enhanced firing irregularity was associated with a smaller proportion of dendrites penetrating the substantia nigra pars reticulata. These results suggest that differences in dendritic morphology contribute to the in vivo firing properties of individual DA neurons, and that the existence of region-specific synaptic connectivity rules that shape firing diversity.